Visco-Elastoplastic Constitutive Fatigue Model for Rocks - Jianhao Liu; Shaoyun Pu; Junying Rao (Advances in Civil Engineering)
The study on the constitutive fatigue model for rocks under cyclic loading has an important significance in rock engineering. In order to study the fatigue properties of rocks under cyclic loading, according to the theory of rheological mechanics and the existing three basic one-dimensional fatigue elements, i.e., elastic, viscous, and plastic fatigue elements, the three-dimensional elastic, viscous, and plastic fatigue elements were constructed. Meanwhile, a fatigue yield criterion for rocks under cyclic loading was proposed, and a three-dimensional nonlinear visco-elastoplastic fatigue constitutive model (NVPFM) for rocks was established by using the flow criterion related to the proposed fatigue yield criterion. Compared with the test results of rocks under cyclic loading, the three-dimensional NVPFM could be used to describe the transient, steady-state, and tertiary creep phases of rocks under cyclic loading.